2019
DOI: 10.5152/iao.2018.3273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin and Dexamethasone on Facial Nerve Neurorrhaphy

Abstract: Journal of International Advanced Otology requires and encourages the authors and the individuals involved in the evaluation process of submitted manuscripts to disclose any existing or potential conflicts of interests, including financial, consultant, and institutional, that might lead to potential bias or a conflict of interest. Any financial grants or other support received for a submitted study from individuals or institutions should be disclosed to the Editorial Board. To disclose a potential conflict of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…Although peripheral motor nerves have regeneration capacity, full healing is not achieved if total nerve laceration is present [Batioglu-Karaaltin et al, 2016]. The outcomes of end-toend anastomosis are not always satisfactory because of poor axonal regeneration and synkinesis [Chu et al, 2018;Edizer et al, 2019]. Therefore, trophic factor transportation to the injury region has been suggested to be beneficial in supporting nerve repair [Alan et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although peripheral motor nerves have regeneration capacity, full healing is not achieved if total nerve laceration is present [Batioglu-Karaaltin et al, 2016]. The outcomes of end-toend anastomosis are not always satisfactory because of poor axonal regeneration and synkinesis [Chu et al, 2018;Edizer et al, 2019]. Therefore, trophic factor transportation to the injury region has been suggested to be beneficial in supporting nerve repair [Alan et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…In total axonal nerve injury, end-toend anastomosis, which is called neurorrhaphy (NR), is the ideal treatment method [Beris et al, 2019]. Various agents, such as melatonin, lipoic acid, and neurotrophic nerve growth factors, have been experimentally used to enhance FN regeneration [Ma et al, 2018;Tekdemir et al, 2018;Edizer et al, 2019]. As steroids decrease the oedema around the nerve and lipoic acid has antioxidant features, both are used in enhancing FN regeneration [Tekdemir et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has possible therapeutic effects for treating neurodegenerative diseases, cardiovascular diseases, and many other clinical complications ( Amer, Othamn, & El-Missiry, 2021 ). Melatonin also shows immunomodulatory consequences which depend on its ability to augment the cytokine levels and antioxidant properties ( Edizer et al, 2019 ; Kuthati et al, 2020 ).…”
Section: Melatonin and Its Functions In Diabetic Neuropathymentioning
confidence: 99%
“…Recent studies using various lesion models of the central and peripheral nervous system have indicated melatonin–induced neuroprotective effects occurring in a dose–dependent manner and unfolding their full magnitude at supraphysiological concentrations around 50 mg/kg in a (systemic) long–term administration ( Gül et al, 2005 ; Shokouhi et al, 2008 ; Atik et al, 2011 ; Li et al, 2014 ). Systemic intraperitoneal administration of melatonin in mice after facial nerve injury has been shown to preserve the thickness of myelin sheaths, whereas given electrophysiological parameters of nerve conduction that included the latency and amplitude of the compound muscle action potentials have remained unaltered ( Tuna Edizer et al, 2019 ). Edizer and colleagues have also observed reduced immunohistochemical reactivity to collagen III and V in the treated nerve as well as minimal immune infiltration and normal structure of axons and neurofilaments ( Tuna Edizer et al, 2019 ); for more details see Table 1 .…”
Section: Melatonin’s Effects On Neuroregenerationmentioning
confidence: 99%
“…Systemic intraperitoneal administration of melatonin in mice after facial nerve injury has been shown to preserve the thickness of myelin sheaths, whereas given electrophysiological parameters of nerve conduction that included the latency and amplitude of the compound muscle action potentials have remained unaltered ( Tuna Edizer et al, 2019 ). Edizer and colleagues have also observed reduced immunohistochemical reactivity to collagen III and V in the treated nerve as well as minimal immune infiltration and normal structure of axons and neurofilaments ( Tuna Edizer et al, 2019 ); for more details see Table 1 . Of note, also topically applied melatonin has been found to support regeneration, yet not at the same level of magnitude as to when the hormone had been administered systemically ( Tuna Edizer et al, 2019 ).…”
Section: Melatonin’s Effects On Neuroregenerationmentioning
confidence: 99%